Cerro de Pasco in the Process of Independence (1819-1824) - Adanaqué Velásquez, Raúl (2010)
The study of Peruvian independence process in the province of Pasco is important because it will help us to understand the colonial liberation movement in the path of the peoples of America. In the case of our country will highlight the human and material contribution of rural residents. The patriotic action was not the result of the expedition of José de San Martin and Simón Bolívar, rather the situation of exploitation of realistic and creole power groups, that settled in the region, especially mining region.